Health Education Prevention and Control of Hypertension in the Elderly in Sei Rotan Village, Batang Kuis Working Area of Puskesmas Batang Kuis Deli Serdang - Liesmayani, Elviera; Khaerunisa, Ismah; Arisman, Yessy (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LP2M) Institut Kesehatan Medistra Lubuk Pakam, 2024)
Hypertension is one of the common health problems in the elderly and has a significant impact on the quality of life and the risk of complications such as cardiovascular disease and stroke. Prevention and control of hypertension in the elderly requires a holistic approach involving promotive, preventive, curative, and rehabilitative efforts. This Community Service activity aims to provide information to the community, especially the elderly, about the prevention and control of hypertension, with an emphasis on lifestyle interventions, pharmacological treatment, and health education. The method used in this community service is Education on Prevention and Control of Hypertension in the Elderly using lecture and discussion methods and blood pressure checks, blood sugar and cholesterol checks. The socialization was attended by 79 participants, which lasted for 2.5 hours. Educational activities were carried out by delivering the main material, discussion as well as a question and answer discussion and closing. In addition, before the material event began, a blood pressure and blood sugar/cholesterol examination was carried out first. The results of this activity, the elderly who attended received education about the knowledge of Prevention and Control of hypertension (healthy lifestyle, stress management, physical activity), and the results of laboratory tests showed that out of 79 elderly people there were 30 people with normal blood pressure, 28 people positive cholesterol and 21 elderly people with positive blood sugar <200 mg/dl. This health education is expected to be able to detect early increases in cholesterol and uric acid and blood sugar in the elderly. In addition, it is also to increase the knowledge of the elderly about the prevention and control of hypertension in the elderly in the Batang Kuis Deli Serdang Health Center.